Predictive value of Chartis measurement for lung function improvements in bronchoscopic lung volume reduction - Johannes Wienker; Rüdiger Karpf-Wissel; Faustina Funke; Christian Taube; Julia Wälscher; Jane Winantea; Sandra Maier; Khaled Mardanzai; Kaid Darwiche (Therapeutic Advances in Respiratory Disease, 2020)
Background: Bronchoscopic lung volume reduction (BLVR) via valve implantation can be achieved by targeting severely hyperinflated and emphysematously destructed lung areas in patients with chronic obstructive lung disease. Lack of collateral ventilation (CV) is important for good outcomes with BLVR. CV can be measured using the catheter-based Chartis system. The aim of this study was to evaluate the correlation between total exhaled volume drained from the target lobe measured by Chartis and clinical outcomes after BLVR in CV-negative patients. Methods: From January 2016 to March 2019, 60 patients were included in this retrospective single-center analysis. Drained volume (TVol) measured by Chartis was recorded and compared with lung function and physical performance parameters. Outcome variables included the percentage change in lung function [forced expiratory volume in 1 s (FEV 1 ), residual volume (RV), and inspiratory vital capacity (IVC)]. Secondary outcomes were the degree of target lobe volume reduction (TLVR), change in 6-min walk distance (6MWD), and change in chronic obstructive pulmonary disease (COPD) assessment test (CAT) score. Results: Drained volume correlated significantly with post-BLVR change in FEV 1 ( r  = 0.663), IVC ( r  = 0.611), RV ( r  = −0.368), and TLVR ( r  = 0.635) (all p  < 0.05). In a priori -defined patient subgroups based on drained volume [<100 ml ( n  = 19), 100−400 ml ( n  = 33), and >400 ml ( n  = 8)]; mean changes in FEV 1 were 2.6%, 17.4%, and 51.3%; in RV were −3.9%, −10.6%, and −23.8%; in IVC were −4.0%, 10.6%, and 62.4%; and in TLVR were 525 ml (39%), 1375 ml (73%) and 1760 ml (100%), respectively. There were no significant correlations between absolute and percentage changes in 6MWD and the CAT score. Lung volume reduction was diagnosed in 32 (53%) cases. Conclusion: Drained volume measured by the Chartis system correlated with functional improvement in CV-negative patients undergoing BLVR. The reviews of this paper are available via the supplemental material section.